2016
DOI: 10.1155/2016/9035745
|View full text |Cite
|
Sign up to set email alerts
|

Increased Macular Pigment Optical Density and Visual Acuity following Consumption of a Buttermilk Drink Containing Lutein-Enriched Egg Yolks: A Randomized, Double-Blind, Placebo-Controlled Trial

Abstract: Purpose. To study the effect of 1-year daily consumption of a dairy drink containing lutein-enriched egg yolks on macular pigment optical density (MPOD) and visual function parameters in elderly subjects with ocular drusen and/or retinal pigment abnormalities. Methods. One hundred and one subjects were recruited to participate in this randomized, double-blind, placebo-controlled parallel intervention trial. Statistical analyses were performed with 46 subjects in the lutein group and 43 in the control group. MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Low values of MPOD at the RMDA test location in our study suggest that light filtration is not a major factor. Other investigators reported both positive 5 and negative 27,31 associations of MPOD regarding aspects of rod-mediated visual tasks distinct from retinoid-limited RMDA used in this study. As mentioned above, an association of delayed RMDA with low MPOD measured with HFP at fixation was found with a small sample and under non-standard stimulus conditions.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Low values of MPOD at the RMDA test location in our study suggest that light filtration is not a major factor. Other investigators reported both positive 5 and negative 27,31 associations of MPOD regarding aspects of rod-mediated visual tasks distinct from retinoid-limited RMDA used in this study. As mentioned above, an association of delayed RMDA with low MPOD measured with HFP at fixation was found with a small sample and under non-standard stimulus conditions.…”
Section: Discussionsupporting
confidence: 51%
“…A positive association of foveal MPOD with BCVA builds on prior research in which tissue-level MPOD was assessed with HFP 6,24,30,31,63,64 and other techniques. 65,66 In younger adults with normal maculas, BCVA is modestly associated with higher MPOD 24 and has been shown to improve 6 to 12 months after supplementation in some studies 6,31,63 but not in others. 30,64 In eyes with variably defined AMD, BCVA improved with supplementation in relation to MPOD in some studies [65][66][67] but not in others.…”
Section: Discussionmentioning
confidence: 70%
“…The AREDS2 formulation with 10 mg lutein/d and 2 mg zeaxanthin/d is now the standard of care for reducing the probability of advanced AMD in patients with substantial risk factors for progression to severe visual loss, and there is even some evidence that subjects receiving AREDS2-type supplements could have stabilization and improvement of best-corrected visual acuity (151,152). However, the AREDS2 failed to show that fish oil supplements had any benefits, and the b-carotene of the original AREDS formula is no longer generally recommended because of potential lung cancer risks.…”
Section: Resultsmentioning
confidence: 99%
“…This was reported in subjects with retinal pigment abnormalities and/or drusen who consumed a lutein-enriched egg drink daily for twelve months. However, this was not found after consumption for 6 months [ 61 ] or 3 months [ 62 ]. With this lutein-enriched egg drink, there was simultaneous supply of docosahexanoic acid that facilitated the incorporation of lutein in the MP.…”
Section: Discussionmentioning
confidence: 99%